Effects of yttria stabilized zirconia (3Y-TZP) percentages on the ZTA dynamic mechanical properties. (May 2015) - Arab, Ali; Ahmad, Zainal Arifin; Ahmad, Roslan
Abstract: Ceramics materials are extensively used in armor applications. Various parameters were considered for selecting the most suitable ceramic materials such as hardness, fracture toughness, and dynamic properties. However, better understanding of the dynamic properties i.e., hardness and toughness required deep insight so as to predict mechanical behavior of ceramic subjected to dynamic loadings. In this paper, these properties were investigated by using different amounts of 3Y-TZP (10–40 wt.%) in zirconia toughened alumina (ZTA) for the purpose of evaluating the relationship between the strength, hardness and fracture toughness of dynamically loaded ceramics. The highest dynamic strength of 4.9 GPa was obtained with the combination of ZTA with 20 wt.% of 3Y-TZP. In addition, the composition also had better hardness and fracture toughness responses in comparison with others. Highlights: Effects of 3Y-TZP on hardness and fracture toughness of ZTA. Measuring the dynamic strength of ZTA with SHPB Finding relation between the hardness and fracture toughness to dynamic strength